Electrochemical stripping features of graphite and its products characterization. Issue 2 (1st February 2017) - Guo, Qin; Huang, Donggen; Luo, Cui; Xiong, Wei; Yang, Tianzi; Quan, Shuiqing; Liu, Le
ABSTRACT: A stable dispersion in mixed solvent of water and N, N-dimethyl formamide (DMF) of graphene was synthesized by one-step electrochemical approach. Here we demonstrate about electrochemical stripping graphite to prepare graphene influence by different electrolytes. The physical and chemical properties of the stripping product had been characterized by using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), UV-Vis spectrophotometer (UV-Vis), Scanning electron microscopy (SEM), Transmission Electron Microscope (TEM) . The characteristic results of XRD showed that it could improve the efficiency of graphite stripping when H2 SO4 was used as electrolyte mother liquid and amount of HNO3 was doped in electrolyte; XPS and FTIR results indicate that the electrochemical stripping products preserve the intrinsic structure of graphene. The results of SEM and TEM shown that the surface morphology of the as-prepared graphene was folded lamellar structure and have good transparency;its thickness varies from 0.8 nm to a few nanometers.